Passive Immunization With a Novel Monoclonal Anti-PrP Antibody TW1 in an Alzheimer’s Mouse Model With Tau Pathology - Boutajangout, Allal; Zhang, Wei; Kim, Justin; Abdali, Wed Ali; Prelli, Frances; Wisniewski, Thomas (Frontiers in Aging Neuroscience, 2021)
Neurofibrillary tangles are a major pathologic hallmark of Alzheimer's disease (AD). A number of studies have shown that amyloid β oligomers (Aβo) and tau oligomers mediate their toxicity, in part, via binding to cellular prion protein (PrPC) and that some anti-PrP antibodies can block this interaction. We have generated a novel monoclonal anti-PrP antibody (TW1) and assessed the efficacy of passive immunization with it in a mouse model of AD with extensive tau pathology: hTau/PS1 transgenic (Tg) mice. These mice were injected intraperitoneally once a week with TW1 starting at 5 months of age. Behavior was assessed at 8 months of age and brain tissue subsequently harvested for analysis of treatment efficacy at 9 months. Mice treated with TW1 did not show any significant difference in sensorimotor testing including traverse beam, rotarod and locomotor activity compared to controls. Significant cognitive benefits were observed with the novel object recognition test in the immunized mice (two-tailed, t-test p= 0.0019). Immunized mice also showed cognitive benefits on the closed field symmetrical maze (day 1 two-tailed t-test p=0.0001; day 2 two-tailed t-test p=0.0015; day 3 two-tailed t-test p=0.0002). Reduction of tau pathology was observed with PHF-1 immunohistochemistry in the piriform cortex by 60% (two-tailed t-test p=0.01) and in the dentate gyrus by 50% (two-tailed t-test p= 0.02) in animals treated with TW1 compared to controls. There was no significant differences in astrogliosis or microgliosis observed between treated and control mice. As assessed by Western blots using PHF-1, the TW1 therapy reduced phosphorylated tau pathology (two-tailed t-test p=0.03) and improved the ratio of pathological soluble tau to tubulin (PHF1/tubulin) (two-tailed t-test p=0.0006). Reduction of tau pathology also was observed using the CP13 antibody in the piriform cortex (two-tailed t-test p=0.02). These results indicate that passive immunization with the TW1 antibody can significantly decrease tau pathology as assessed by immunohistochemical and biochemical methods, resulting in improved cognitive function in a tau transgenic mouse model of AD.